PEMINANGAN DALAM ADAT SUKU TAJIO DI DESA SINEY KECAMATAN TINOMBO SELATAN KABUPATEN PARIGI MOUTONG DALAM PRESPEKTIF HUKUM ISLAM - Sri Ajirna; Muh. Syarif Hasyim; Sahran Raden (Familia: Jurnal Hukum Keluarga, 2020)
This study aims by using qualitative methods with data collection techniques, namely interviews, observation, verification in order to obtain data that is truly valid and can be accounted for. The results of this study indicate that the marriage in the adat of the Tajio Tribe in Siney Village, Tinombo Selatan District, Parigi Moutong Regency is to open the tajalang to open the road, that is, the man will tell his desire to propose to the woman but with satire words, then Nalolo Tevulang Nombosi is looking for a day or It is a good month to meet the family of the woman who wants to be married to, the next stage is to open the first tejarita, namely the man comes to the woman's house to discuss further the matchmaking plan and the last marriage process is tevea nelili, which is sprinkling yellow rice on the man's family This is a sign that the woman's family has officially accepted the proposal of the male party and the view of Islamic law on the marriage of the Tajio Tribe in Siney Village, Tinombo Selatan District, Parigi Moutong Regency is not against Islamic Law and even in accordance with Islamic Law because of the marriage in The traditions of the Tajio Tribe in Siney Village, South Tinombo District, Parigi Moutong Regency contain elements of faith, elements of worship and contain elements of akhlakul karimah.